Effect of laminarin and chitosan gel formulations on the treatment of hydrofluoric acid induced corneal burns in the rabbits - (:unkn) unknown (ECOLE NATIONALE VETERINAIRE TOULOUSE, 2008)
Corneal burns were induced in 36 New Zealand white rabbits by instillation in both eyes of 0.05 mL of 2% hydrofluoric acid (HF) for 60 seconds. Following this, the eyes were irrigated with 500 mL isotonic saline (ISOT) and then the rabbits were divided into 4 treatment groups (1) = 9 rabbits each) including: laminarin solution (LS), chitosan hydrogel (CHG), chitosan hydrogel containing laminarin (CHG+L) and ISOT as the control. For each treatment group, one drop of each regimen was instilled 2 times a day and for periods of 2, 7 and 14 days respectively. Thus, 3 rabbits were used for each treatment period in each treatment group. The eyes were clinically examined immediately after the chemical burning and at days 1, 2, 7 and 14 of the follow up periods. The animals were euthanatized at the end of the follow-up periods and eyes were processed for histopathological examination. Clinical and histopathological results revealed that while LS or ISOT was effective, CHG and CHG+L were not effective in the treatment of HF corneal burns. LS had a better therapeutic effect than ISOT. CHG and CHG+L treatment had no accelerating effect on the healing of: corneal erosion throughout the experimental procedures.
Keywords: chitosan; laminarin; isotonic saline; HF induced corneal burn; rabbit; CALCIUM GLUCONATE; EYE BURNS; MACROPHAGES; DERIVATIVES; EMERGENCY; EFFICACY; PH